Battle pass capitalism. (February 2021) - Joseph, Daniel
This article investigates the origin, circulation and consumption of a new commodity – the "battle pass" – in the complex ludic economies of contemporary digital games. The article dives deep into the history and political economy of battle royale shooters and the game Apex Legends (2019), a free-to-play example of the genre monetized in part by a battle pass. Inspired and in dialogue withNieborg and Poell's (2018) theory of platformization, this article asks questions related to how digital games like this operationalize their status as 'contingent commodities'. The article then engages in an 'app walk-through' (Light et al., 2018 ) of Apex Legends, analysing its vision, operating model and governance. The focus here is on revealing the 'mediator characteristics' that structure in-game commodities like avatar skins, loot boxes and the battle pass. There is then a discussion and theorization of these monetization strategies and the industry-wide tendencies for consumerism they signal. A key takeaway is that digital consumption in games is at once both easy to 'see' but also highly abstracted, making it very difficult to pull apart what people are actually consuming when they engage with the monetization layer of contemporary digital games.